2007
DOI: 10.1590/s0100-879x2006005000105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surfactant protein B polymorphisms of healthy term newborns with preterm newborns having respiratory distress syndrome

Abstract: Polymorphisms and mutations in the surfactant protein B (SP-B) gene have been associated with the pathogenesis of respiratory distress syndrome (RDS). The objective of the present study was to compare the frequencies of SP-B gene polymorphisms between preterm babies with RDS and healthy term newborns. We studied 50 preterm babies with RDS (inclusion criteria -newborns with RDS and gestational age between 28 and 33 weeks and 6 days), and 100 healthy term newborns. Four SP-B gene polymorphisms were analyzed: A/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…This result differs from a study by another laboratory where the AG genotype was considered to be a risk factor for RDS (7). In our 2007 study on a population of healthy term and preterm newborns from the city of São Paulo, we did not find a protective effect of the AG genotype (30).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This result differs from a study by another laboratory where the AG genotype was considered to be a risk factor for RDS (7). In our 2007 study on a population of healthy term and preterm newborns from the city of São Paulo, we did not find a protective effect of the AG genotype (30).…”
Section: Discussioncontrasting
confidence: 95%
“…In 2007, we studied the same four polymorphisms in a group of 100 healthy term babies and a group of 50 preterm babies with RDS (30). When race was analyzed separately, among the white individuals, the GG genotype was only found in the RDS group.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of preliminary investigations into the genetic susceptibility of neonatal RDS (1,15). The effect of hereditary factors on neonatal RDS was previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results indicate that intron 4 length variants affect SP-B mRNA splicing and that this may contribute to lung disease (6). Polymorphisms and mutations in the SP-B gene are associated with the pathogenesis of respiratory distress (15). Several studies have demonstrated that deletion variants of intron 4 affect SP-B gene expression (3,4,6); however, SP-B intron 4 variant frequencies have no detectable association with RDS in Brazilian and Finnish populations (1,16).…”
Section: Discussionmentioning
confidence: 99%
“…Results of another study have shown the incidence of SP-B deficiency in African Americans to be higher than in Caucasian Americans (12). The SP-B gene mutation has been shown to be associated with some respiratory diseases, including neonatal RDS, acute respiratory distress syndrome, congenital pulmonary alveolar proteinosis, adult chronic obstructive pulmonary emphysema and chronic lung diseases in children (1315). …”
Section: Discussionmentioning
confidence: 99%